Business Development Intervention and Performance of Aquaculture: A Case of Business Groups in Lagos State, Nigeria - Nurudeen Afolabi Sofoluwe; Olajumoke Olufunmilayo Oyeniyi; Moruff Sanjo Oladimeji (Bina Nusantara University, 2022)
Businesses in Small and Medium Enterprises (SMEs) are considered crucial to the development of societies. Hence, development interventions from international agencies are introduced to these groups to achieve developmental objectives. However, the importance of such intervention to the overall performance of the enterprises is yet to be examined. The research assessed the contribution of the intervention to the production capacity of SMEs. It also examined the business volume and value of sales of their products and contribution to employment opportunities. Then, the factors influencing participation in the project by the SMEs were also analyzed. Survey data were collected through a structured questionnaire. A stratified random sampling technique was employed to select the business groups. Descriptive statistics and probit regression methods were utilized to analyze the data. The results show an improvement in the production capacity of the participating business groups. Relatively, the average production capacity of medium enterprises is higher compared to the small business groups. The volume and value of sales and employment opportunities created through the financial intervention increase the performance of SMEs in the aquaculture business sector. Education and membership in the association are also found to be significant factors (p < 0,05). The factors affect business group participation in the intervention.